2021
DOI: 10.16899/jcm.804329
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemisinin Sağlık Çalışanlarında Kaygı, Öfke, Uyku ve Duygu Düzenleme ile İlişkisi

Abstract: Objective: Epidemic diseases have caused significant mental responses throughout the society and especially healthcare professionals, as well as those who have been infected. Healthcare professionals have a big role in the fight against the new coronavirus infection . When the literature is reviewed in terms of risky professions, as the cases increase, the psychological influence has increased significantly among the healthcare professionals dealing with the care of patients as an occupational group. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…Also in this study, it was found that the gender variable had no effect on the severity of insomnia. However, there are studies in the literature where the ISI median and mean score of female are higher than male (Salcan & Sarıkaya, 2020;Söğütlü et al, 2021). Similarly, in this study, female academicians' total ISI score average was found to be higher than male.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Also in this study, it was found that the gender variable had no effect on the severity of insomnia. However, there are studies in the literature where the ISI median and mean score of female are higher than male (Salcan & Sarıkaya, 2020;Söğütlü et al, 2021). Similarly, in this study, female academicians' total ISI score average was found to be higher than male.…”
Section: Discussionsupporting
confidence: 50%
“…Questionnaire Form: It includes some socio-demographic questions such as age, gender, academic title of people in line with the literature (Salcan & Sarıkaya, 2020;Scotta et al, 2020;Söğütlü et al, 2021) by the researchers.…”
Section: Data Collection Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research explored the emotional consequences of COVID-19 on HWSs, showing high levels of burnout among these workers [ 9 ] and, in particular, high levels of emotional exhaustion [ 10 ]. The amount of work and time pressure also led to serious difficulties in emotional regulation for these workers [ 11 ]. These data appear even more worrisome if we consider the importance of emotional labor required of HWSs and the necessity of the appropriate emotional regulation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies by other authors prove that people who are often subjected to fear as a condition are at risk for it becoming a feature and will contribute to occurrence of anxiety situations (social, somatic, etc.) [27,28]. The COVID-19-related pandemic caused fear and anxiety among people around the world [3,10,13,23].…”
Section: Discussionmentioning
confidence: 99%